Assessment of knowledge and abilities in using an Automated External Defibrillator by students of Wroclaw nonmedical colleges - Czyż, Rafał; Górniak, Izabela (Journal of Education, Health and Sport, 2017)
The automated external defibrillator (AED) is modern and seemingly difficult in applying device, which correctly used in sudden cardiac arrest (SCA) indeed increasing vitcim’s chances to survive. Growing availability of these devices should be connected with a growth of the social awareness about correct using of this equipment. The aim of this study was to evaluate the knowledge level about automated external defibrillator among randomly chosen nonmedical students from Wroclaw colleges. Study group constituted of 204 students, with 123 women and 81 men aged 22.3 ± 1.5 years. All of respondents gave consent to voluntary and anonymous filling of the author's questionnaire. Straight majority of respondents (92%) took participate in first aid training, however not all of them had heard about AED. Only 38% of examined students is correctly pointing what the defibrillation is. Majority of the students (78%) is declaring the readiness of AED use, if such a need will appeared, however as far as the 49% of students isn't able to describe of correct arranging AED electrodes on the patient’s chest. Fact that only 14% of respondents are able to elaborate the abridgement of PAD also seems alarming. The knowledge about AED and applying it in the population of Wroclaw nonmedical colleges students is insufficient. It’s important to spread information about AED on all types of first aid trainings. PAD program should be more promoted in public campaigns in order to increase the level of social awareness.